2007
DOI: 10.1002/pdi.1056
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a specialist nurse prescriber on diabetes in‐patient service delivery

Abstract: The aim of this study was to evaluate the impact of a diabetes specialist nurse (DSN) prescriber on insulin and oral hypoglycaemic agent medication errors, length of hospital stay, and patients' ability to self‐manage their diabetes whilst in hospital. The setting was six wards in a single United Kingdom district general hospital trust. The standard in‐patient care of a convenience sample of diabetic patients treated with insulin and/or oral hypoglycaemic agents was evaluated before (n = 187) and after (n = 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 12 publications
2
28
0
Order By: Relevance
“…Line managers and medical practitioners were equally distributed between primary and secondary care. This decrease in student recruitment from primary care is consistent with previous studies which have reported a gradual shift from primary to secondary care (Ahuja, 2009;Courtenay et al, 2007Courtenay et al, , 2012. This can perhaps be attributed to changes in legislation in 2006, and with non-medical controlled drug prescribing aligned with medical prescribing recruitment from secondary care is likely to remain high.…”
Section: Discussionsupporting
confidence: 80%
“…Line managers and medical practitioners were equally distributed between primary and secondary care. This decrease in student recruitment from primary care is consistent with previous studies which have reported a gradual shift from primary to secondary care (Ahuja, 2009;Courtenay et al, 2007Courtenay et al, , 2012. This can perhaps be attributed to changes in legislation in 2006, and with non-medical controlled drug prescribing aligned with medical prescribing recruitment from secondary care is likely to remain high.…”
Section: Discussionsupporting
confidence: 80%
“…The final selection consisted of 21 studies [383940414243444546474849505152535455565758]. Examples of integrated care interventions included patient education by specialist nurses, structured patient-oriented care coordination, the use of a patient registry to support multidisciplinary team work and practice nurse involvement in shared medical appointments.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes medicines management was part of the DSN intervention in all of the inpatient studies, but only one used the skills of the nurse prescriber to identify diabetes medication and management errors, and prescribe, where deemed necessary. 22 Secondary outcome measures included in two inpatient studies were patient satisfaction and qualityof-life; 2,22 the effect on patient knowledge was included in one study. 2 The effect of the DSN intervention on nursing and medical …”
Section: Inpatient Studiesmentioning
confidence: 99%
“…2,[19][20][21][22][23] In the five papers that presented formal statistical analysis, these results were highly significant (Table 1). 2,19,[21][22][23] Other results…”
Section: Length Of Hospital Staymentioning
confidence: 99%